Pregnancy and olfaction: a review - Cameron, E. Leslie (Frontiers in Psychology, 2014)
Many women report a heightened sense of smell during pregnancy. Accounts of these anecdotes have existed for over one hundred years, but scientific evidence has been sparse and inconclusive. In this review I examine the literature on olfactory perception during pregnancy including measures of self-report, olfactory thresholds, odor identification, intensity and hedonic ratings and disgust. Support for a general decrease in olfactory thresholds (increase in sensitivity) is generally lacking. There is limited evidence that some suprathreshold measures of olfactory perception, such as hedonic ratings of odors, are affected by pregnancy, but these effects are idiosyncratic. In this review I explore the hypotheses that have been put forth to explain changes in olfactory perception during pregnancy and provide suggestions for further research.